RASIONALISASI JARINGAN STASIUN CURAH HUJAN PADA DAERAH ALIRAN SUNGAI TUKAD MATI - Putu Doddy Heka Ardana; I Gusti Made Sudika; I Wayan Angga Hadinata (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
The hydrological component is the main component in planning water infrastructure. The quality and quantity of rainfall data recorded at each rain post is the most crucial component in hydrological analysis, so it is necessary to analyze the rationalization of the rain station network to obtain an effective and efficient one. This research was conducted in the Tukad Mati Watershed, which has an area of 44,667 km2, with the length of the main river reaching 22,429 km, and there are six rain stations spread across the watershed. Rationalization analysis was carried out using two methods, namely the WMO (World Meteorological Organization) and Kagan-Rodda methods. The analysis using the WMO standard found that all rain stations were less than the minimum density. Meanwhile, from the results of the analysis using the Kagan-Rodda method with a smoothing error (Z1) of 9.069% and an interpolation error (Z3) of 7.989%, it is recommended that four selected rain stations out of six rain stations, namely Ngurah rain station, Sanglah rain station, Sading rain station, and Kapal rain station.